A VALIDATED STABILITY-INDICATING REVERSE-PHASE HIGH-PERFORMANCE LIQUID CHROMATOGRAPHY METHOD FOR DACLATASVIR, IDENTIFICATION AND CHARACTERIZATION OF DEGRADATION PRODUCTS USING LC-ESI-QTOF-MS - SNEHAL V WARGHADE,; KAILAS G BOTHARA, (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: The objective of this study was to report the stability of antiviral drug, daclatasvir (DCV) based on the information obtained from forced degradation studies and characterization of degradation products (DPs) by tandem mass spectrometry (MS/MS) analysis. Methods: Chromatographic separation was achieved on Shimadzu liquid chromatography (LC) 20 AD high-performance LC system with photodiode array detector having Kromasil C18 (250 mm×4.6 mm×5 μm) with isocratic elution of a mobile phase composed of ammonium acetate buffer (pH 4.5) and acetonitrile in a ratio of 50:50 at 315 nm. The drug was subjected to forced hydrolytic, oxidative, photolytic, and thermal stress in accordance with the ICH guideline Q1A (R2). The drug showed degradation under acidic and basic hydrolytic conditions by forming two DPs. The DPs were characterized using LC– MS/MS studies and the pathways of fragmentation are proposed. Validation of the developed method was carried out in accordance with ICH guidelines. Results: Two DPs were identified, DP-1 as (S)-1-((S)-2-(5-(4’-(2-((S)-1-((S)-2-((methoxycarbonyl)amino)-3-methylbutanoyl)pyrrolidin-2-yl)-1H-imidazol-5-yl)-[1,1’-biphenyl]-4-yl)-1H-imidazol-2-yl)pyrrolidin-1-yl)-3-methyl-1-oxobutan-2-aminium and DP-2 as (S)-2-(5-(4’-(2-((S)-1-((S)-2- ((methoxycarbonyl)amino)-3-methylbutanoyl)pyrrolidin-2-yl)-1H-imidazol-5-yl)-[1,1’-biphenyl]-4-yl)-1H-imidazol-2-yl)pyrrolidin-1-ium. Conclusion: The method proved to be simple, accurate, precise, specific, robust, and less time consuming and can be applied for the determination of DCV in bulk and marketed formulation.